KAJIAN FAKTOR PERILAKU KESEHATAN IBU NIFAS YANG MEMPENGARUHI KUNJUNGAN MASA NIFAS DI INDONESIA - Zalukhu, Junimiserya; Girsang, Bina Melvia (Jurnal Kesehatan Masyarakat, 2023)
The phenomenon that occurs in Indonesian society is that there is a gap between the coverage of postpartum visits and the visit standards set by the Indonesian Ministry of Health, namely a minimum of four postpartum visits. The standard of four visits is to maximize the recovery period for the reproductive organs of the postpartum woman. This indicator is the government's effort to provide postpartum maternal health services in accordance with quality standards as an effort to reduce the Maternal Mortality Rate (MMR). The method used in this study was a systematic literature review using the PICOS approach (to determine inclusion and exclusion criteria) and the PRISMA approach (to screen articles). The database used to search for articles is Google Scholar with the help of the Publish or Perish software. The results obtained from the ten research articles, namely, 80% of the articles provide an overview of postpartum visits that still apply three visits, and 60% of the articles provide an overview of the frequency of complete visits which is higher than incomplete visits. The majority of health behavior factors are influenced by predisposing factors, namely attitudes and knowledge. Through this research it is hoped that it can encourage health workers to provide solutions to existing problems related to the lack of coverage of postpartum visits, so that postpartum visits become more optimal in all regions in Indonesia.